2019
DOI: 10.1038/s41379-019-0249-1
|View full text |Cite
|
Sign up to set email alerts
|

HPV-negative tumors of the uterine cervix

Abstract: Human papillomaviruses (HPV) are the causative agents of virtually all cervical carcinomas. Nevertheless, a small proportion of cervical cancer are negative for HPV, although the significance of this finding remains unclear. We aimed to provide insight into the differential clinico-pathological characteristics of this unusual subset of HPV-negative cervical cancer. We performed HPV-DNA detection using a highly sensitive PCR test (SPF10) and p16 immunostaining in 214 cervical carcinomas specimens from women tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
88
5
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(105 citation statements)
references
References 40 publications
11
88
5
1
Order By: Relevance
“…A meta-analysis of 2838 cervical cancer cases from 17 studies revealed that HPV positivity correlated with better prognosis (OS: HR=0.610, p =0.001; disease-free survival: HR=0.362, p <0.001) ( 68 ). To date, three other studies have reached the same conclusion that HPV-negative cervical cancer is associated with poor prognosis ( Table 3 ) ( 57 59 ). Nevertheless, a 10-year follow-up study of 204 patients with cervical cancer revealed that the 5-year OS rate of HPV-negative and HPV-positive patients was 82% and 58% ( p =0.003), respectively, indicating that HPV infection was significantly correlated with poor OS of patients ( 69 ).…”
Section: Prognosis Of Human Papillomavirus-negative Cervical Cancermentioning
confidence: 72%
See 1 more Smart Citation
“…A meta-analysis of 2838 cervical cancer cases from 17 studies revealed that HPV positivity correlated with better prognosis (OS: HR=0.610, p =0.001; disease-free survival: HR=0.362, p <0.001) ( 68 ). To date, three other studies have reached the same conclusion that HPV-negative cervical cancer is associated with poor prognosis ( Table 3 ) ( 57 59 ). Nevertheless, a 10-year follow-up study of 204 patients with cervical cancer revealed that the 5-year OS rate of HPV-negative and HPV-positive patients was 82% and 58% ( p =0.003), respectively, indicating that HPV infection was significantly correlated with poor OS of patients ( 69 ).…”
Section: Prognosis Of Human Papillomavirus-negative Cervical Cancermentioning
confidence: 72%
“…HPV-negative patients are prone to develop advanced FIGO stage and lymphatic space invasion prior to diagnosis, resulting in poor prognosis ( Table 3 ) ( 57 , 58 ). A multicenter study revealed that 62.5% of HPV-negative adenocarcinomas were stage II or higher, while 83.7% of usual type cases were stage I at diagnosis, which concurred with previous studies ( 60 ).…”
Section: Clinical Features Of Human Papillomavirus-negative Cervical mentioning
confidence: 99%
“…The need for this specific update, which does not affect the TNM categories, is that HPV-associated cervical cancer has a more favorable prognosis than HPVindependent cervical cancer. [6][7][8] Approximately 10% of cervical carcinomas are HPV-negative. 6,7 In one study, patients who had HPV-negative tumors were older, had more advanced disease at diagnosis, and were more frequently diagnosed with nonsquamous histology; moreover, they had a significantly worse disease-free survival (60 months vs 132 months) and overall survival (77 months vs 154 months) compared with women who had HPV-positive tumors.…”
Section: Nxmentioning
confidence: 99%
“…A small proportion of CCs (<5%) are truly HPV-negative after sensitive HPV assessment. These tumors are more frequently of the non-squamous subtype, diagnosed at advanced stages, show higher prevalence of lymph node metastases, and have an impaired prognosis [7,8]. HPV-negative CCs have distinct molecular characteristics that show similarities with endometrial cancer, while having a significantly higher epithelialmesenchymal transition mRNA score and a lower frequency of the APOBEC mutagenesis signature compared to their HPV-positive counterparts [9,10].…”
Section: Introductionmentioning
confidence: 99%